2017
DOI: 10.1016/j.anai.2017.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and reproducibility of nasal biomarkers in patients with allergic rhinitis after allergen challenge chamber exposure

Abstract: clinicaltrials.gov Identifier: NCT00297843.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 21 publications
(22 reference statements)
2
35
0
Order By: Relevance
“…On each exposure visit, one half of the subjects were challenged without any treatment, while the other half received NP. The concentration of grass pollen in the ACC was monitored continuously and kept stable for the duration of the challenges [19].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On each exposure visit, one half of the subjects were challenged without any treatment, while the other half received NP. The concentration of grass pollen in the ACC was monitored continuously and kept stable for the duration of the challenges [19].…”
Section: Methodsmentioning
confidence: 99%
“…It was previously used in preclinical experiments as a cytotoxic marker from bronchoalveolar lavage fluid, enabling detection of the inflammatory response in the lungs of rats after exposure to particulate matter, and was, therefore, included in this study. The biomarkers were evaluated from nasal filter eluates pre and post allergen challenge [21]. The cytokines eotaxin, interleukin-3 (IL-3), IL-4, IL-5, IL-6, macrophage inflammatory protein-1β, and tumor necrosis factor α were analyzed in the samples collected pre, 2 h post, and 18 h post challenge, using multiplex assays by Meso Scale Discoveries (Rockville, MD, USA).…”
Section: Biomarker and Cell Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has published 2 case series describing a rush subcutaneous immunotherapy (SCIT) schedule administered using a subcutaneous infusion pump [1,2], in which the maintenance dose was reached after 3 visits. This type of rush protocol with SCIT provides a rapid clinical response, improved adherence, and increased cost-effectiveness owing to the lower number of visits and doses [3][4][5].…”
Section: Safety Of An Ultrarush (4 Hours) Subcutaneous Immunotherapy mentioning
confidence: 99%
“…Nasal cytology is a convenient method that is very useful in clinical practice, mainly in the diagnostic and prognostic work-up of patients with rhinitis [2]. In addition, it has been reported that the nasal eosinophil count correlates better with symptom severity and IgE level [3,4].…”
mentioning
confidence: 99%